ANALISIS EFESIENSI DAN IDENTIFIKASI FAKTOR SOSIAL, EKONOMI DAN TEKNIS YANG MEMPENGARUHI KONVERSI USAHATANI JERUK KE USAHATANI KOPI DI KECAMATAN BARUSJAHE KABUPATEN KARO - Albina Ginting; Hotden L Nainggolan; Musfrianto H Ginting (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2018)
The aim of this study are; a) to determine the efficiency level of citrus farming and conversion to coffee farming in Barusjahe District, b) to identify social, economic and technical factors affecting conversion of citrus farming to coffee farming in Barusjahe District, and this research uses descriptive data analysis method. The results of research are; a) average income level of citrus farming Rp. 14,867,110/ha/ year < average income of coffee farming Rp.17.675.996 /ha/ year, and efficiency of citrus farming (R/ C: 2.52) < efficiency of coffee farming (R/C: 4,43), b) Social factor that is public acknowledgment is the main reason of 33% of respondents to convert citrus farming to coffee farming. And the economic factor that is the price is the main reason 33.3% respondents, the conversion of citrus farming to coffee farming. As well as technical factors namely the maintenance process is the main reason for 56.67% of farmers respondents to convert citrus farming to coffee farming in Barusjahe District. Based on the research results suggested; a) for the government to conduct continuous counseling for farmers of coffee farming so that its production is increasing, b) so that citrus farmers do better maintenance and maintenance in order to optimize their production, c) so that farmers use pesticide in accordance with recommended dosage, to reduce the cost pesticides, d) for farmers to pay attention to the concept of sustainable agriculture in converting  land  from citrus farming to coffee farming in Barusjahe District so farmers' income can be sustainable.